2017
DOI: 10.1620/tjem.242.281
|View full text |Cite
|
Sign up to set email alerts
|

Higher Serum Levels of Osteoglycin Are Associated with All-Cause Mortality and Cardiovascular and Cerebrovascular Events in Patients with Advanced Chronic Kidney Disease

Abstract: Patients with chronic kidney disease (CKD) have markedly increased rates of major adverse cardiovascular and cerebrovascular events (MACCEs) and mortality. Therefore, identifying early biomarkers predicting clinical outcomes in patients with CKD is critical. We aimed to determine whether osteoglycin, a basic component of the vascular extracellular matrix, was associated with MACCEs or all-cause mortality, using data from a prospective randomized controlled study, K-STAR (Kremezin STudy Against Renal disease pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…While the work model of OGN in GC is not clear and needs to be further explored. Moreover, OGN, as one of the biologically active elements of the vascular extracellular matrix, could be tested in plasma/serum and acted as a biomarker in disease [ 29 , 30 ]. For instance, serum OGN was an independent risk predictor for patients with chronic kidney disease [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the work model of OGN in GC is not clear and needs to be further explored. Moreover, OGN, as one of the biologically active elements of the vascular extracellular matrix, could be tested in plasma/serum and acted as a biomarker in disease [ 29 , 30 ]. For instance, serum OGN was an independent risk predictor for patients with chronic kidney disease [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 21 references for 15 RCTs met the eligibility criteria of the present study (Figure 1). (Sanaka et al, 1988;Koide et al, 1991;Owada et al, 1997;Nakamura et al, 2004;Morita et al, 2005;Marier et al, 2006;Schulman et al, 2006;Shoji et al, 2007;Asano et al, 2008;Konishi et al, 2008;Takahashi et al, 2008;Yorioka et al, 2008;Akizawa et al, 2010;Toyoda et al, 2014;Wu et al, 2014;, 2015; Cha et al, 2016;Schulman et al, 2016;Baek et al, 2017;Cha et al, 2017;Schulman et al, 2018)…”
Section: Resultsmentioning
confidence: 99%
“…[624] and Matejas et al [625] showed that EGR1, NR4A1, SIK1, CCN1, CEBPD (CCAAT enhancer binding protein delta), SOCS2, RGS2, KL (klotho), SOCS3, MMP1, CXCR4, CCN2, FST (follistatin), OGN (osteoglycin), CTLA4, KLF4, PTGER3, HBEGF (heparin binding EGF like growth factor), CCL2, OSM (oncostatin M), ERBB4, TNFSF11, MSTN (myostatin), ADAMTS1, CALCR (calcitonin receptor), INHBB (inhibin subunit beta B), EPO (erythropoietin), IL10, CEBPB (CCAAT enhancer binding protein beta), FOXO1, DKK1, GAS1, NPHP3, FGF2, ATF3, ANGPT2, SOCS1, IL1RAP, C9ORF72, BASP1, AKR1B10, SLC22A12, ACHE (acetylcholinesterase), TREM2, SCD (stearoyl-CoA desaturase), GCK (glucokinase), FOXP3, SLC22A2, EPHB2, LPL (lipoprotein lipase), ANGPTL8, HCN2, HSPA8, MB (myoglobin), KCNJ11, GLIS2, TNFSF13, LSS (lanosterol synthase), GAS6, AGRN (agrin), ACE2, NLRP6, DPEP1, TIMP3, CHI3L1, RASAL1, FAT1, GPBAR1, TREH (trehalase), CFB (complement factor B), FNDC5, HLA-G, MMP9, C4A and LAMB2 were associated with kidney disease, but these genes might be novel targets for NAFLD. [657], SOCS3 [658], MMP1 [659], CXCR4 [660], RASD1 [661], SLC7A11 [662], OGN (osteoglycin) [341], KLF4 [663], IL1RL1 [664], CCL2 [665], EPO (erythropoietin) [666], IL10 [667], ESR2 [668], VIP (vasoactive intestinal peptide) [669], FOXC1 [670], FOXO1 [671], S100B [672], DKK1 [673], SOCS1 [674], C9ORF72 [675], CTCFL (CCCTC-binding factor like) [676], S1PR2 [677], ACHE (acetylcholinesterase) [678], TREM2 [679], EPHB2 [680], LPL (lipoprotein lipase) [681], P2RY2 [682], ACE2 [683], CHI3L1 [684], HLA-G [685] and MMP9 [686] are found in cerebrovascular diseases, but these genes might be novel targets for NAFLD.…”
Section: Discussionmentioning
confidence: 99%